John Dewey on Education / Selected Writings - Archambault Reginald D. (The University Of Chicago Press, 1964)
In this collection the writer has assembled John Dewey's major writings on education. Preface, Introduction, Philosophy and Education, Ethics and Education, Aesthetics and Education, Science and Education, Psychology and Education, Society and Education, Principles of Pedagogy.